Assessment of Phytodiversity of Kukrail Forest, in the Perspective of Urban Development - Gangwar, Prachi; Lavania, Seshu (Indian Forester, 2019)
The anthropocentric development process has led to presumptive changes in biodiversity. This study deals with the effect of the urban developmental process on phytodiversity of Kukrail Reserve Forest of Lucknow. The study area is within town limits and is influenced by all sorts of biotic interferences. Transect survey was conducted and an inventory of trees species was made for accessing the phytodiversity of the region and for studying the phytosociological parameters. A total of 27 species with 1367 individuals were enumerated in total 2.84 ha area. The values of ShannonWiener diversity index obtained in this study are between 0.46-1.02 which indicates low diversity of species, as compared to the values reported in tropical forests. The values of Shannon-Wiener diversity index and Simpson's index are highest for the transect which was in comparatively lesser disturbed site. The highest stand density is 565 trees/ha, found in the area with comparatively less disturbance, while the lowest stand density of 291 trees/ha is found in most disturbed site.